2015
DOI: 10.1371/journal.pone.0130136
|View full text |Cite
|
Sign up to set email alerts
|

SerpinB2 (PAI-2) Modulates Proteostasis via Binding Misfolded Proteins and Promotion of Cytoprotective Inclusion Formation

Abstract: SerpinB2 (PAI-2), a member of the clade B family of serine protease inhibitors, is one of the most upregulated proteins following cellular stress. Originally described as an inhibitor of urokinase plasminogen activator, its predominant cytoplasmic localisation suggests an intracellular function. SerpinB2 has been reported to display cytoprotective properties in neurons and to interact with intracellular proteins including components of the ubiquitin-proteasome system (UPS). In the current study we explored the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 59 publications
(100 reference statements)
0
28
0
Order By: Relevance
“…It can comprise up to 1% of total cellular protein in monocytes [6, 7]. Recent data have implicated SERPINB2, also known as PAI-2 (plasminogen activator inhibitor-2), in type III angioedema and a new functional analysis revealed one of its key functions is to modulate proteotoxic stress [8, 9]. …”
Section: 0 Introductionmentioning
confidence: 99%
“…It can comprise up to 1% of total cellular protein in monocytes [6, 7]. Recent data have implicated SERPINB2, also known as PAI-2 (plasminogen activator inhibitor-2), in type III angioedema and a new functional analysis revealed one of its key functions is to modulate proteotoxic stress [8, 9]. …”
Section: 0 Introductionmentioning
confidence: 99%
“…It was shown that it exhibits cytoprotective propertiesin neurons. It is one of the most regulated proteins after cellular stress [24]. The TXNIP gene encodes thioredoxininteracting proteins, which are important for glucose metabolism [25].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental models of PAI-2 deficiency exhibit accelerated DVT resolution without significantly affecting fibrinolysis [205,206]. PAI-2 is primarily retained intercellularly where it binds misfolded proteins, but can be abundantly secreted by pro-inflammatory macrophages [207,208], and acts to regulate many aspects of circulating monocyte and macrophage behavior [209,210]. Within apolipoprotein E gene-deleted mice, hyperlipidemia resulted in a significantly elevated level of PAI-1 and an undetectable uPA concentration, so fibrinolysis and thrombus resolution were severely impaired [211].…”
Section: Fibrinolysismentioning
confidence: 99%